Analyzing risk-related information seeking behavioral intention and risk perception of wildfires: the High Park Fire Burn Area - Mokry, Melissa M., author; Trumbo, Craig, advisor; Kim, Jangyul, committee member; Abrams, Katie, committee member; Hoffman, Chad, committee member; Schumacher, Russ, committee member (Colorado State University. Libraries, 2019)
This study assessed risk-related information seeking behavioral intention and dual-process risk perception within the context of wildfires. Particularly, the study focused on utilizing a combined risk-related information seeking model with concepts originating from the planned risk information seeking model (PRISM), a framework of risk information seeking (FRIS), and the risk information seeking and processing model (RISP). The key concepts utilized included: past risk-related information seeking, self-efficacy, response efficacy, dual-process risk perception (affective and cognitive risk perception, perceived hazard knowledge, information needs, and behavioral intention. A survey (N=432; 60.8% response rate) was disseminated to the High Park Fire Burn Area, west of Fort Collins, Colorado which experienced a wildfire in 2012. The survey revealed the importance of including dual-process risk perception in risk-related information seeking models and highlighted its influence on past risk-related information seeking and risk-related information seeking behavioral intention. Response efficacy was correlated with self-efficacy, following suit to other risk-related information seeking studies. Cognitive risk perception was correlated with affective risk perception, suggesting a bi-directional relationship between the two concepts. Individuals were more likely to seek wildfire information in the past if they did not have enough knowledge about the hazard. Moreover, individuals are more likely to base their risk perception on their emotions, particularly when facing a wildfire. The results from the survey revealed that the exploratory path had a better model fit than the confirmatory path model, yet both provided important findings related to risk-related information seeking behavioral intention and dual-process risk perception. This study reaffirmed the need for theoretical improvement related to current information needs, particularly in relation with perceived hazard knowledge and risk-related information seeking behavioral intention. There were inconsistencies with current information needs throughout the study, following suit with the literature and calls for further refinement of the concept. Implications and future research efforts are also noted and discussed such as the importance of tailored messaging and a communication campaign.